ANALISIS TINGKAT PENCEMARAN UDARA DI KAWASAN PERKOTAAN: STUDI KASUS DKI JAKARTA - Dicky Triawarman; Alfianus Telaumbanua; Faredzi Dhika Saputra; Octavia Adiguna; Rendi Kurniawan (SINERGI : Jurnal Riset Ilmiah, 2026)
Air pollution in urban areas is an increasingly serious environmental issue driven by rising industrial and transportation activities. This study aims to analyze air pollution levels in Jakarta using key parameters such as Particulate Matter (PM2.5 and PM10), Carbon Monoxide (CO), Nitrogen Dioxide (NO₂), Sulfur Dioxide (SO₂), and Ozone (O₃). Measurements were conducted over a one-week period at monitoring sites representing industrial, commercial, and residential areas, as well as green open spaces. The methodology involved direct ambient air sampling using High Volume Air Samplers (HVAS) and impingers, followed by laboratory analysis via spectrophotometry and gravimetry. Results indicate that PM2.5 concentrations in industrial areas reached 78.4 µg/m³, exceeding the 55 µg/m³ standard set by Government Regulation No. 22 of 2021. The average Air Pollution Standard Index (ISPU) across the monitoring sites fell into the 'Unhealthy' category. Motor vehicle emissions (62.3%) and industrial activities (28.7%) were identified as the dominant sources of pollution. The study recommends strengthening public transportation systems, expanding green open spaces, and tightening industrial emission regulations as measures to mitigate urban air pollution.